Implementasi Personal Selling sebagai kontributor peningkatan kulitas Komunikasi Pemasaran Pada Era Copid 19: Manajemen pemasaran - Tedi Pitri, SIP., MM (Ekonomedia, 2021)
In today’s marketing era Copid 19 , consumers seem to have known about marketed products and no longer need explanation from a salesperson. The interaction between company and target consumers can be marketed through new media such as email, Facebook, WA, Instagram, and other forms. Such situations need to be in-depth researched in terms of whether personal selling contribution is still needed in marketing communication activities. Considering the uniqueness and personal selling advantages turns out that personal selling is an important partner that can not be replaced by other forms of marketing communications even if there is exposure to new media to promote products. The specialty of personal selling lies in its ability to interact directly to improvise the sales process through person to person communication.